Un bénévolat jeunesse pour favoriser la participation sociale des aînés : l'expérience des participants au projet intergénérationnel Sunny Action. Issue 1 (2nd January 2020) - Fortier, Julie; Belley-Ranger, Émilie
Abstract : The Sunny Action project aims to bridge the gap between generations by inviting young people aged 12 to 18 to volunteer in residential centers during the summer months. The young people accompany the elderly during the leisure activities and thus promote a context of social participation. This paper describes the intergenerational experience of young people and elders through volunteering and social participation within the Sunny Action project. During the summer of 2015 the authors conducted a case study on the Sunny Action project. They carried out semi-structured interviews with 11 elderly people and the project coordinator and conducted two focus groups with 14 young volunteers. The following themes were discussed: the motivations and expectations, the attitudes required, the benefits obtained, and satisfaction with the project. Results show that the Sunny Action project generates several benefits for young people, but also for seniors and their living environment.